Konsep Mahabbah dan Permasalahan Cardiomyopathy Takotsubo - Selfia Ferjiani (Gunung Djati Conference Series, 2023)
Love is an incarnation that is not easy to explain, the greatest power as well as the deadliest weakener. Without love could we be born, without love it feels like a colorless life. Then what about love, which people often say to people who experience it, is called falling in love but all they get is the fall, then it causes various psychological problems such as heartbreak which leads to emotional and physical stress. The purpose of this writing is to make readers aware that love is never wrong, if lovers get lost then love will not. This writing method uses literature study or library research. The conclusion can be drawn that mahabbah i.e. loving God is the best choice.